CODE MIXING USED BY IQBAAL RAMADHAN ON THE HAHAHA TV YOUTUBE CHANNEL - Aryani, Fadhilla Arum; Budiwaty, Suci (Universitas Gunadarma, 2024)
This research investigates the types and motives of code-mixing employed by Iqbaal Ramadhan in the YouTube videos